Sosialisasi Penggunaan Aplikasi ELSA Speak dalam Pembelajaran Pengucapan Bahasa Inggris di SMK - Dewi Untari; Helmi Agus Salim; Hamliyah; Ayub Felan Maulana; Irianti Cantikha (JPM: Jurnal Pengabdian Masyarakat, 2024)
Correct pronunciation is a crucial component in mastering the English language, especially for students in inclusive schools who face diverse learning challenges. The lack of interactive learning media often hinders students from developing their pronunciation skills independently. The ELSA Speak application, powered by artificial intelligence, is introduced as a solution to help improve students' pronunciation skills more effectively. This community service aims to promote the use of the ELSA Speak application to teachers and students at SMK Inklusi TPA Jember, with the goal of enhancing the quality of English pronunciation learning.  The community service partners in this program are teachers and students of SMK Inklusi TPA Jember. The method of implementation is socialization of the use of ELSA Speak Application in English pronunciation Learning. The promoting is conducted through face-to-face sessions and hands-on practice using the application to improve pronunciation skills. The results of this activity show an increase in both students' and teachers' understanding of the benefits of the application for pronunciation learning, as well as students' motivation to use technology.